Contact Geometrical Study for Top Emitting 980 nm InGaAs/GaAsP Vertical-Cavity Surface Emitting Lasers - Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Geometrical contacts of a double mesa structure with 16 rows ×15 columns arrays of top emitting GaAs based 980 nm vertical cavity surface emitting lasers (VCSELs) are fabricated and characterized. In this paper, 5 strained In0.22Ga0.78As/Ga0.9AsP0.1 quantum wells (QWs) within λ/2 thick cavity have been employed. The top and the bottom epitaxially grown mirrors are based on the linear graded Al0.9Ga0.1As/GaAs distributed Bragg reflectors (DBRs) with 20.5 and 37 periods, respectively. Static parameters including threshold currents, rollover currents, maximum optical output power and wall-plug efficiency are extracted from light out power-current-voltage (LIV) of VCSELs with fixed oxide aperture diameter of ∅ 6 μm and various mesa2 diameters. In addition, spectral emission for 980 nm VCSELs of oxide aperture between ∅ 6 and 19 μm and with fixed ∅ 6 μm and different bias currents are analyzed. The highest optical output power of around 33 dBm is observed at bias current of 0.8 mA for short−reach optical interconnect applications.